Microplasma‐Induce Liquid Chemistry for Stabilizing of Silicon Nanocrystals Optical Properties in Water. Issue 2 (9th December 2013) - Mitra, Somak; Švrček, Vladimir; Mariotti, Davide; Velusamy, Tamilselvan; Matsubara, Koiji; Kondo, Michio
<x xml:space="preserve">Abstract</x> In this report, we demonstrate stabilization of photoluminescence (PL) properties of environmentally and biologically friendly silicon nanocrystals (SiNCs) in water through atmospheric pressure radio‐frequency (RF) microplasma processing at room temperature. The PL of the SiNCs is enhanced after microplasma processing, which involves three‐dimensional engineering of SiNCs directly in water avoiding degradation by surface functionalization. Moreover, we compare the RF microplasma process with direct‐current microplasma processing, whereby the two approaches lead to very similar SiNCs optical properties and surface characteristics. The induced unique chemistry and SiNCs stability in water have wide implications for the SiNCs processability and applications in energy devices, biology and medicine.<inline-graphic xlink:href="ark:/27927/pgg4sq5xm77" content-type="ppap201300097-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />